Sleep Quality of Diabetic Patients with Metabolic Syndrome, is There a Difference? - Savas Karatas; Aysun Işıklar (Baiman Bauntung Batuah Center, 2020)
Poor sleep quality is a prevalent health problem among patients with diabetes. Metabolic syndrome (MetS) is common in type 2 diabetic patients and associated with morbidity and mortality. We aimed to investigate sleep quality among type 2 diabetes patients according to their metabolic syndrome status. This was an analysis of data collected from 189 adult type 2 diabetic patients. The patients divided into two groups (metabolic and non-metabolic) based on the presence of MetS. Anthropometric measurements, blood pressure, and serum glucose, lipid levels were collected. The Pittsburgh Sleep Quality Index (PSQI) calculated for all patients. There was no significant difference in subjective sleep quality scores between the two groups (p > 0.05). However, there was a significant difference in sleep latency scores between the two groups; the scores of patients with MetS were lower than those of patients without MetS (p = 0.010, p < 0.05).Sleep quality was low in 57.1% (n = 108) of patients with diabetes. Poor sleep is common among diabetic patients, but in this study, metabolic syndrome existence not associated with sleep quality in type 2 diabetic patients.